Medicina, chirurgia e politica nell'Ottocento toscano: l'archivio di Ferdinando Zannetti - Donatella, Lippi (Firenze University Press, 2003)
The biography and the works of Ferdinando Zannetti, physician, surgeon, politician and outstanding figure in nineteenth-century Tuscany acquire new light through the organisation and inventorying of the papers from his archive. The history of medicine and surgery of this period is enriched by new data, making it possible to enter into the daily exercise of the profession. The evidence of Zannetti as a military doctor and organiser of the health service during the wars of independence also offers a fascinating new slant on the history of the Risorgimento. The political life of Florence and Tuscany are relived in the framework of the laborious construction of the new State.